2019
DOI: 10.1002/jeab.543
|View full text |Cite
|
Sign up to set email alerts
|

An implementation of punishment in the evolutionary theory of behavior dynamics

Abstract: An implementation of punishment in the evolutionary theory of behavior dynamics is proposed, and is applied to responding on concurrent schedules of reinforcement with superimposed punishment. In this implementation, punishment causes behaviors to mutate, and to do so with a higher probability in a lean reinforcement context than in a rich one. Computational experiments were conducted in an attempt to replicate three findings from experiments with live organisms. These are (1) when punishment is superimposed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
1
13
1
Order By: Relevance
“…One is to study the effect of punishment superimposed on single schedules of reinforcement. In McDowell and Klapes's (2019) implementation of punishment in the ETBD, the punishment of a target behavior causes phenotypes in the target class to mutate with a specific probability. This mutation may result in a phenotype mutating out of the class altogether, thereby decreasing the probability that a behavior from that class will be emitted again.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One is to study the effect of punishment superimposed on single schedules of reinforcement. In McDowell and Klapes's (2019) implementation of punishment in the ETBD, the punishment of a target behavior causes phenotypes in the target class to mutate with a specific probability. This mutation may result in a phenotype mutating out of the class altogether, thereby decreasing the probability that a behavior from that class will be emitted again.…”
Section: Discussionmentioning
confidence: 99%
“…The wide range of phenomena for which the theory accounts, and various untested predictions of the theory, are also discussed in these articles. Not included in these articles, however, is McDowell and Klapes' (2019) recent implementation of punishment in the evolutionary theory. They studied the behavior of AOs working on concurrent schedules of reinforcement with punishment superimposed on one or both alternatives, and found that the behavior of the AOs was consistent with the behavior of live organisms in similar experiments.…”
Section: The Evolutionary Theory Of Behavior Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational models, on the other hand, are extremely rare. McDowell and colleagues have developed an intriguing and fruitful research project simulating behavior selection in a computer environment (McDowell, 2013, McDowell & Klapes, 2019. Their implementations have to make explicit the implicit assumptions adopted by verbal theories and in the process they are able to not only specify these parameters, but also show how the parameters interact when the programs run, and to determine the limits of the model, such as how much variation is needed for a selection-by-reinforcement to be adaptive (McDowell, 2017).…”
Section: Discussionmentioning
confidence: 99%